BRICS: LATINAMERICAN PROJECTION - E. . Astakhov (Ибероамериканские тетради)
The paper analyses recent trends in foreign policy of Latin-American countries, in particular their approaches to the cooperation with BRICS. The main attention is paid to the analysis of Brazilian policy towards BRICS. Brazil is the only country which represents Latin-American continent in BRICS and has excellent possibilities to enter “the club of the Great Powers”.